Pendidikan Aqidah dalam Perspektif Hadits - mayangsari R, galuh nasrullah kartika (GRADUATE SCHOOL OF PALANGKA RAYA STATE ISLAMIC INSTITUTION, 2017)
This paper focuses on the study of hadith relating to educational beliefs (Aqeedah) and efforts that should be made to foster the potential of natural child through certain methods, in order to practice the faith we have in order to achieve happiness in this world and hereafter, as the implementation of a belief in the unity of God. The most important matter in educational beliefs (Aqeedah) is the first developing work ethic and motivation of faith, Islam and Ihsan. Second, consistency in the Faith. Third, understand natural phenomena and social phenomena through understanding the laws as a reflection of faith and Islamic theology. The methods used in the education of aqidah are the method of imitation/model, method of habituation, wisdom and mauidzah hasanah methods. The family is the first in the formation of aqidah environment for children. Parents are the key element for the establishment of tawhid in the family, so that everyone is required to have an understanding of monotheism and practice well, so that it can provide children with the values of monotheism and material support. Kids can see their parents as role models who provide knowledge as well as experience, and guidance.